Compact-size ultra-wideband circularly polarized antenna with stable gain and radiation pattern - Xu, Rui (2022)
A novel ultra-wideband (UWB) circularly polarized (CP) antenna array with sequential phase feed is proposed in this article. The element implements a multiresonance monopole to achieve UWB CP radiation. To investigate the CP operating mechanism, characteristic mode analysis is used to provide different modes at various frequencies. The simulated characteristic mode analysis results show that this element can realize good CP at three independently adjustable frequencies (2.4, 3.8, and 5.8 GHz). By combining these three frequencies, a UWB CP antenna element is realized from 2.02 to 6.03 GHz for axial ratio (AR) less than 3.0 dB. Because the main radiating region of this element changes at different frequencies, a compact 2 × 2 array, whose profile is only 0.09λ (where λ is the wavelength in free space at the lowest operating frequency), is designed and optimized to achieve higher realized gain and stable radiation pattern. Subsequently, a prototype of this array is fabricated and measured. Measured results demonstrate an overlapping bandwidth of 120.9% from 1.8 to 7.3 GHz, in terms of the-10 dB reflection coefficient bandwidth and 3 dB AR bandwidth. This array has the advantages of simple structure, compact size, high gain, and stable pattern within the entire operating band.